Support for information processing, information acquisition, and age as factors influencing self-regulated learning in adolescent girls - Aguilar-Salcedo, Brigitte; Orihuela-Anaya, Rita; Calderón-Calderón, Roxana; Zamora-Ortiz, Marieth; Tito-Valderrama, Juanita; Dominguez-Vergara, Julio (Frontiers in Education, 2025)
IntroductionStudents have adopted a more active role in their learning process, which has facilitated the implementation of strategies aimed at enhancing their academic outcomes. The literature shows that these strategies help explain self-regulated learning, although some demonstrate a higher predictive capacity than others. Within this framework, the present study aims to identify the model that most accurately explains self-regulated learning.Materials and methodsA quantitative, cross-sectional explanatory study with non-probabilistic sampling was conducted. The sample consisted of 249 female adolescents from first to fifth year of secondary education in Lima, Peru. The Self-Regulated Learning Questionnaire and the ACRA Scale were administered.ResultsModel 3 was significant, with an adjusted R2 of 0.603. The variables information-processing support, information acquisition, and age significantly explained self-regulated learning, although age showed a lower explanatory weight.DiscussionThe results confirm that information-processing support has the greatest influence on self-regulated learning, whereas age is not a determining factor. Additionally, for this study, information acquisition ranked second in influence. These findings guide educational institutions in providing more targeted interventions focused on strategies for information-processing support and information acquisition, achieving better outcomes when applied from the early stages of secondary education for adolescent girls. Nevertheless, the study's limitations should be considered, as it was conducted on a sample of females with specific characteristics from Lima, Peru.